2019
DOI: 10.1299/transjsme.19-00245
|View full text |Cite
|
Sign up to set email alerts
|

Center of gravity velocity estimation using lower limb joint power during walking

Abstract: This paper presents examination of a proposed method for center of gravity (COG) velocity estimation during walking using information obtained from lower limb motion measurements. Lower limb joints and muscles around these joints are used during walking. Gait velocity changes according to lower limb muscle activity. Some earlier reports of relevant studies have suggested that lower limb muscle weakness reduces the walking rate, which increases the probability of falling. Therefore, the relation between the COG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
1
0
Order By: Relevance
“…Thus, complex exercises require multiple models for each phase. For example, in a study that estimated walking speed using lower limb joint power, two models were developed for the stance phase because the joint power differed greatly between the single support phase and the double support phase (Saito et al, 2019). In future work, in order to apply the proposed model to different types of movement, we will consider human motion from the viewpoint of kinematics and kinetics to develop a model that is suitable for an arbitrary movement.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, complex exercises require multiple models for each phase. For example, in a study that estimated walking speed using lower limb joint power, two models were developed for the stance phase because the joint power differed greatly between the single support phase and the double support phase (Saito et al, 2019). In future work, in order to apply the proposed model to different types of movement, we will consider human motion from the viewpoint of kinematics and kinetics to develop a model that is suitable for an arbitrary movement.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that the joint moments and power in lower limbs have a strong relationship with walking speed (Olney et al, 1991;Olney et al, 1994;Winter, 2009). The authors previously proposed a walking model that uses the center-of-gravity (CoG) velocity and lower limb joint power during walking and demonstrated that the lower limb joint power that influences CoG movement differs in each gait phase (Saito et al, 2019). Joint motion is caused by muscles pulling on bones.…”
Section: Introductionmentioning
confidence: 99%